Study of single crystal growth and semiconducting properties of intercalated and doped transitional metal dichalcogenides - Toh, Minglin. (2013)
Layered materials consist of covalently bonded layers separated by van der Waals gaps. They have attracted tremendous interest due to their superior charge transport properties and two-dimensional structural stabilities. The wide range of layered materials for instance the graphite and metal dichalcogenides possesses excellent optical and electronics properties. The above underlines the vast potential of layered materials utilization in wide-ranging applications. However under certain conditions, specific layered materials interact readily with atoms or molecules resulting in the intercalant species occupying the van der Waals gaps. Drastic change in the layered materials properties due to intercalation of alkali metal atoms, or organic molecules, into the layered materials has been reported. In this work, metal dichalcogenide single crystals of SnS2, WSe2, HfSe2, SnSe2 TiSe2 and NbSe2 with crystal sizes up to fifteen millimeters had been synthesized. Such sizes of the single crystals obtained from vapor phase indicated on the optimum crystal growth conditions employed. Optical imaging, Scanning Electron Microscopy, Energy Dispersive X-ray analysis, Atomic Force Microscopy and Transmission Electron Microscopy characterizations on cleaved layered materials showed two-dimensional atomically flat morphology, molecular steps and correct stoichiometry of the compounds. Ultra Violet-Visible light spectroscopy in transmission mode indicated on the direct or indirect band gap values for the intrinsic single crystals.